SOME WEED SPECIES AFFECTING SOYBEAN NODULATION AND NODULE FUNCTION - Chaniago, Irawati; Taji, Acram; Kristiansen, Paul; Jessop, Robin (AGRIVITA, Journal of Agricultural Science, 2012)
Experiments aimed at examining the effect of aqueous extracts of three weed species on nodulation and nodule function of soybean cv. Melrose have been carried out at the Laboratory of Plant Physiology and Biotechnology, Department of Agronomy and Soil Science, University of New England, Australia. Aqueous extracts of fresh weed material (Amaranthus powellii, Cyperus rotundus and Paspalum dilatatum) at the concentration of 10% (w/v) were added to a minus-nitrogen Hoaglandâs nutrient solution in which the soybean plants were grown with 14 hours day length, day and night temperatures of 28 and 20Â°C, respectively, light intensity of 790 mmol/m2/s, and the relative humidity of 65%. The plants were kept for three weeks prior to the measurement of activity of nitrogenase enzyme and ammonium content of the root nodules. Results demonstrate that all weed extracts reduced the nodulation and nitrogenase activities (ARA) of soybean cv. Melrose. Amaranth was most inhibitory to nitrogenase enzyme activity. However, amaranth extract was less inhibitory than nutgrass extract in total ammonium content.